DNA methylation patterns of banana leaves in response to Fusarium oxysporum f. sp. cubense tropical race 4 - Jing-yao LUO; Xiao-lei PAN; Tie-cheng PENG; Yun-yun CHEN; Hui ZHAO; Lei MU; Yun PENG; Rui HE; Hua TANG (Journal of Integrative Agriculture, 2016)
Fusarium wilt of banana, which is caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), is a serious soil-borne fungal disease. Now, the epigenetic molecular pathogenic basis is elusive. In this study, with methylation-sensitive amplification polymorphism (MSAP) technique, DNA methylation was compared between the leaves inoculated with Foc TR4 and the mock-inoculated leaves at different pathogenic stages. With 25 pairs of primers, 1 144 and 1 255 fragments were amplified from the infected and mock-inoculated leaves, respectively. DNA methylation was both changed and the average methylated CCGG sequences were 34.81 and 29.26% for the infected and the mock-inoculated leaves. And DNA hypermethylation and hypomethylation were induced by pathogen infection during all pathogenic stages. Further, 69 polymorphic fragments were sequenced and 29 of them showed sequence similarity to genes with known functions. And RT-PCR results of four genes indicated that their expression patterns were consistent with their methylation patterns. Our results suggest that DNA methylation plays important roles in pathogenic response to Foc TR4 for banana.